The Effect of Training Methods and Power on Shooting Accuracy of Porma Football School Players in Kudus Regency (Journal of Physical Education and Sports, 2022)
The purpose of this research is to compare training with fixed targets with training with changing targets at SSB PORMA Kudus Regency. Objectives 1) To investigate the impact of fixed and variable target training methods on soccer shooting accuracy. 2) Analyzing the difference between the effects of high and low power on the accuracy of soccer shooting. 3) Examining the influence of training methods and strength on the shooting accuracy of SSB Porma soccer players in Kudus Regency. Research Procedure Utilize a 2 x 2 factorial design for your experiments. The factorial design consists of two independent variables: training method and leg muscle strength. This study included 24 16-year-old SSB PORMA Kudus Regency players as participants. The results indicated that the Training method (Fixed Targets and Changed Targets) yielded a value of 0.035 (<0.05). Then, shooting accuracy is affected by the fixed target training method and the variable target training approach. Leg Muscle Power (high and low) has a sig value of 0.017 (<0.05). Then, high power and low power influence the soccer shot accuracy of SSB Porma players in Kudus Regency. Training Method * Power has a sig value of 0.000 (<0.05). The conclusion of changing the target training strategy is markedly improved shooting accuracy. The lower leg muscular strength was much better than the high power. There is an interaction between training methods and strength on the soccer shot accuracy of SSB Porma, Kudus Regency players.